STRATEGIES FOR EXPANDING THE POPULARIZATION OF TESTED PROFICIENT SPEAKERS OF INDONESIAN AT THE LAMPUNG PROVINCIAL LANGUAGE OFFICE - Anggraini Saputri; Budhi Waskito; Yanuarius Yanu Dharmawan; Haninun; Afrizal Nilwan (Journal of Management, Business and Social Sciences, 2023)
This study aims to design a strategy to increase the popularity of Indonesian speakers who are proficient and tested at the Lampung Provincial Language Office. The study used a qualitative method and a descriptive approach and analytical testing using SWOT analysis. The Lampung Provincial Language Office experienced problems in achieving the implementation of activities to increase the popularity of proficient and tested Indonesian speakers in the community. The achievement of the activities that were not achieved could not meet the target resulting in an increase in the target in the following year. Therefore, in 2022 the target number of UKBI testers will increase by 38.49%. Based on the research that has been done, it can be concluded that the failure to achieve the target is influenced by the location of the language office in Lampung Province, the revision of the Indonesian language carried out and the highest scores are at the level of service quality and digitization of the Lampung provincial Language office. Then suggestions were obtained, namely, there was a need to change correctional strategies in increasing the popularity of Indonesian speakers who were proficient and tested with several efforts, namely making written regulations and sanctions such as laws so that speakers of the language had to obey and carry out activities to increase and popularity. Therefore, the implementation of the strategy to increase the popularity of proficient and tested Indonesian speakers can be carried out and achieve the predetermined targets.